Merger Control in the EEC / A survey of European Competition Laws - Verloop Peter (Kluwer Law And Taxation Publishers, 1993)
This book contains a concise description of both the EEC law with regard to mergers and acquisitions at Community level and the relevant national laws and regulations in Belgium, Denmark, France, Germany, Ireland, Italy, the Netherlands, Spain an the United Kingdom. Introduction, Belgium, Denmark, France, Federal Republic of Germany, Ireland, Italy, The Netherlands, Spain, United Kingdom, EEC.